Twin–twin transfusion and laser therapy. Issue 2 (April 2016) - Behrendt, Nicholas; Galan, Henry L.
Abstract : Purpose of review: Twin-to-twin transfusion syndrome (TTTS) is an uncommon, but dangerous, complication of monochorionic diamniotic twin gestations. The purpose of this review is to provide an update on the evolving treatments in TTTS as it pertains primarily to laser photocoagulation, as well as to provide recently published information on outcomes. Recent findings: The Solomon laser technique, in which selective fetoscopic laser photocoagulation is first performed and then followed by laser of the vascular equator from one side of the placenta to the other, reduces TTTS complications of twin anemia–polycythemia syndrome and recurrent TTTS. The addition of fetal echocardiography to the historical staging of TTTS adds important information that may guide future therapies. The postlaser ablation rate of neurodevelopmental delay in TTTS has recently been reported to be 14%. Cotwin demise is a significant complication of untreated TTTS and survival carries a 25% risk of cystic periventricular leukomalacia, middle cerebral artery infarction, and injury to other central nervous system structures as noted by neuroimaging. Summary: Laser therapy for TTTS is clearly the only therapy that halts the disease process, allows both fetuses an opportunity to survive and protects a surviving cotwin in the event of the demise of one twin. Laser techniques have evolved greatly over the last 25 years and recent reports with the addition of the Solomon technique appearing to reduce some postlaser complications (twin anemia–polycythemia sequence and recurrent TTTS). Future focus of TTTS therapy should be centered on understanding the pathophysiology of the disease better with improvement in staging of the disease and on comparison of different laser techniques with the overall goal of not only increasing twin survival rates but also reducing long term neurodevelopmental morbidity.